2021
DOI: 10.1016/j.conbuildmat.2021.123289
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of monolithic silica-cellulose aerogel applying a sustainable sodium silicate precursor

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…It can be seen that among the three aerogel composites, MCFF@SiO 2 ‐1.5 has the largest specific surface area, although its average diameter of micropores and mesopores are larger than those of MCFF@SiO 2 ‐1 and MCFF@SiO 2 ‐0.5, which is mainly due to the in‐situ formation of the largest amount of silica aerogel in MCFF@SiO 2 ‐1.5, which is confirmed by the above TGA analysis. Combined with the SEM images (Figure 3b–d), it is confirmed that the silica particles covering the collagen fibers is indeed silica aerogel 30,40 . Because of the existence of silica aerogels in the three MCFF@SiO 2 , especially, the average pore diameter of nanometer scale (Table 1) is smaller than the free diameter of air (about 70 nm), their microporous and mesoporous structure hinder the heat transfer of the gas and greatly reduces the thermal conductivity 41 .…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…It can be seen that among the three aerogel composites, MCFF@SiO 2 ‐1.5 has the largest specific surface area, although its average diameter of micropores and mesopores are larger than those of MCFF@SiO 2 ‐1 and MCFF@SiO 2 ‐0.5, which is mainly due to the in‐situ formation of the largest amount of silica aerogel in MCFF@SiO 2 ‐1.5, which is confirmed by the above TGA analysis. Combined with the SEM images (Figure 3b–d), it is confirmed that the silica particles covering the collagen fibers is indeed silica aerogel 30,40 . Because of the existence of silica aerogels in the three MCFF@SiO 2 , especially, the average pore diameter of nanometer scale (Table 1) is smaller than the free diameter of air (about 70 nm), their microporous and mesoporous structure hinder the heat transfer of the gas and greatly reduces the thermal conductivity 41 .…”
Section: Resultsmentioning
confidence: 58%
“…And the asymmetric stretching vibration of CH 2 appeared at 2950 cm −1 , while peaks at 1634, 1538, and 1450 cm −1 are corresponding to CO stretching vibration, NH bending vibration (amide II), and CH bending vibration, respectively 28,29 . In addition, from the FT‐IR spectrum of SiO 2 aerogel, it can be seen that the peak appeared at 2950 cm −1 is the characteristic peak of CH, and the peak around 1253 cm −1 is the stretching vibration of SiC, indicating that SiCH 3 is successfully grafted to the surface of the silica aerogel by HMDS 30,31 . The peak around 1084 cm −1 can be attributed to the stretching vibration of SiOSi bond, and the peak at 950 cm −1 can be attributed to the bending vibration of the SiOH group.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In such a way, smaller nanoparticles can be synthesized from shorter chain alkylsilane. 21 As mentioned, other silica sources are inorganic materials, such as silicon tetrachloride, 22 , 23 olivine, 24 , 25 and sodium silicate solution. 15 , 26 , 27 Sodium silicate as an economical and available precursor can be an excellent source for the synthesis of silica-based nanoparticles.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 99%